Enhanced photocatalytic hydrogen evolution in deionized/natural seawater and removal of organic pollutants using the heterostructure of CuO/Cu2O nanoparticles under visible light - Kangutkar, Raju S.; Walko, Priyanka; Nayaka, Girish Praveen; Nigam, Sandeep; Majumder, Chiranjib; Manjanna, Jayappa (Langmuir, 2026)
Water splitting for hydrogen production and reducing water pollution using solar light are part of the Sustainable Development Goals, which require highly active photocatalytic materials. The heterostructures have demonstrated remarkable photocatalytic advantages in visible light. Herein, we report microwave-assisted green synthesis of CuO/Cu2O nanoparticles using Tridax plant leaf extract. The synthesized nanoparticles were characterized by using PXRD, UV-DRS, Raman spectroscopy, XPS, PL, TRPL, FE-SEM, HR-TEM, BET, and photocurrent. The photocatalytic water splitting performance of CuO/Cu2O and CuO was measured under visible light (lambda >= 420 nm) irradiation using methanol as a sacrificial reagent in DI water and natural seawater. The H2 evolution rates in DI water for CuO/Cu2O and CuO are 2043.21 and 970.09 mu mol g-1 h-1 with apparent quantum efficiency (AQE) values of 5.60 and 2.66 %, respectively. In natural seawater, the H2 evolution rates are 2599.29 and 1370.54 mu mol g-1 h-1 with AQE values of 7.12 and 3.75 %, respectively. The rate of H2 evolution slightly increased in natural seawater. Also, the degradation of the methylene blue dye was examined here, and the efficiency of CuO/Cu2O was determined to be 97 % under natural sunlight. Electrocatalytic H2 evolution was also studied here by using linear sweep voltammetry. Tafel slope values for CuO/Cu2O and CuO are 153 and 250 mV dec-1, respectively. The lowest Tafel value of CuO/Cu2O indicates a faster rate of reaction, thereby producing easier charge separation and lowering the electron-hole recombination due to the presence of surface defects, smaller particle size, enhanced crystallinity, and the synergistic effect between Cu2O and CuO.